In-Situ High-Resolution Transmission Electron Microscopy Investigation of Overheating of Cu Nanoparticles - Chen, Chunlin; Hu, Ziyu; Li, Yanfen; Liu, Limin; Mori, Hirotaro; Wang, Zhangchang (Scientific reports, 2016)
Synthesizing and functionalizing metal nanoparticles supported on substrates is currently the subject of intensive study owing to their outstanding catalytic performances for heterogeneous catalysis. Revealing the fundamental effect of the substrates on metal nanoparticles represents a key step in clarifying mechanisms of stability and catalytic properties of these heterogeneous systems. However, direct identification of these effects still poses a significant challenge due to the complicacy of interactions between substrates and nanoparticles and also for the technical difficulty, restraining our understanding of these heterogeneous systems. Here, we combine in situ high-resolution transmission electron microscopy with molecular dynamics simulations to investigate Cu nanoparticles supported on graphite and Cu 2 O substrates and demonstrate that melting behavior and thermal stability of Cu nanoparticles can be markedly influenced by substrates. The graphite-supported Cu nanoparticles do not melt during annealing at 1073 K until they vanish completely, i.e. only the sublimation occurs, while the Cu 2 O-supported Cu nanoparticles suffer melting during annealing at 973 K. Such selective superheating of the Cu nanoparticles can be attributed to the adsorption of a thin carbon layer on the surface of the Cu nanoparticles, which helps guide further stability enhancement of functional nanoparticles for realistic applications.